Ruxolitinib cream for treatment of vitiligo: a randomised, controlled, phase 2 trial. Issue 10244 (11th July 2020) - Rosmarin, David; Pandya, Amit G; Lebwohl, Mark; Grimes, Pearl; Hamzavi, Iltefat; Gottlieb, Alice B; Butler, Kathleen; Kuo, Fiona; Sun, Kang; Ji, Tao; Howell, Michael D; Harris, John E
Summary: Background: Vitiligo is a chronic autoimmune disease resulting in skin depigmentation and reduced quality of life. There is no approved treatment for vitiligo repigmentation and current off-label therapies have limited efficacy, emphasising the need for improved treatment options. We investigated the therapeutic potential of ruxolitinib cream in patients with vitiligo and report the efficacy and safety results up to 52 weeks of double-blind treatment. Methods: We did a multicentre, randomised, double-blind, phase 2 study for adult patients with vitiligo in 26 US hospitals and medical centres in 18 states. Patients with depigmentation of 0·5% or more of their facial body surface area (BSA) and 3% or more of their non-facial BSA were randomly assigned (1:1:1:1:1) by use of an interactive response technology system to receive ruxolitinib cream (1·5% twice daily, 1·5% once daily, 0·5% once daily, or 0·15% once daily) or vehicle (control group) twice daily on lesions constituting 20% or less of their total BSA for 24 weeks. Patients in the control group in addition to patients in the 0·15% once daily group who did not show a 25% or higher improvement from baseline in facial Vitiligo Area Scoring Index (F-VASI) at week 24 were re-randomised to one of three higher ruxolitinib cream doses (0·5% once daily, 1·5% once daily, 1·5% twice daily). Patients in the 0·5% once daily, 1·5% once daily, or 1·5% twice daily groups remained at their original dose up to week 52. Patients, investigators, and the study sponsor (except members of the interim analysis and primary endpoint analysis data monitoring teams) remained masked to treatment assignment throughout the study. The primary endpoint was the proportion of patients achieving a 50% or higher improvement from baseline in F-VASI (F-VASI50) at week 24, assessed in the intention-to-treat population. The study is registered with ClinicalTrials.gov, NCT03099304 . Findings: Between June 7, 2017, and March 21, 2018, 205 patients were screened for eligibility, 48 were excluded and 157 patients (mean age, 48·3 years [SD 12·9]; 73 [46%] male and 84 [54%] female) were randomly assigned to either an intervention group or the control group. 32 (20%) of 157 were assigned to the control group, 31 (20%) to the 0·15% once daily group, 31 (20%) to the 0·5% once daily group, 30 (19%) to the 1·5% once daily group, and 33 (21%) to the 1·5% twice daily group. F-VASI50 at week 24 was reached by significantly more patients given ruxolitinib cream at 1·5% twice daily (15 [45%] of 33) and 1·5% once daily (15 [50%] of 30) than were treated with vehicle (one [3%] of 32). Four patients had serious treatment-emergent adverse events (one patient in the 1·5% twice daily group developed subdural haematoma; one patient in the 1·5% once daily group had a seizure; one patient in the 0·5% once daily group had coronary artery occlusion; and one patient in the 0·5% once daily group had oesophageal achalasia), all of which were unrelated to study treatment. Application site pruritus was the most common treatment-related adverse event among patients given ruxolitinib cream (one [3%] of 33 in the 1·5% twice daily group; three [10%] of 30 in the 1·5% once daily group; three [10%] of 31 in the 0·5% once daily group; and six [19%] of 31 in the 0·15% once daily group)with three [9%] of 32 patients showing application site pruritis in the control group. Acne was noted as a treatment-related adverse event in 13 (10%) of 125 patients who received ruxolitinib cream and one (3%) of 32 patients who received vehicle cream. All treatment-related adverse events were mild or moderate in severity and similar across treatment groups. Interpretation: Treatment with ruxolitinib cream was associated with substantial repigmentation of vitiligo lesions up to 52 weeks of treatment, and all doses were well tolerated. These data suggest that ruxolitinib cream might be an effective treatment option for patients with vitiligo. Funding: Incyte.